Ethical Dimensions of Cross-Cultural Communication : Exploring the NLP Approach in Student Exchange Programs - Nisa A.A. Silitonga; Selly F. Sitompul; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the ethical considerations in cross-cultural communication within student exchange programs, focusing on the application of Neuro-Linguistic Programming (NLP) techniques such as mirroring, rapport building, reframing, and anchoring. These methods were analyzed for their effectiveness in enhancing understanding and reducing miscommunication among students from diverse cultural backgrounds. Data was collected using interviews and questionnaires, revealing that NLP strategies facilitated better adaptation, trust, and collaboration. The Findings highlight that students' responses predominantly fell into positive categories, with Strongly Agree (20.67%) and Agree (79.33%), showing a high level of alignment with the statements presented in the questionnaire. Notably, there were no Neutral (0%), Disagree (0%), or Strongly Disagree (0%) responses recorded, indicating unanimous agreement with the ideas conveyed. These results suggest a strong consensus among students, reflecting their shared perspectives and high levels of agreement on the topics discussed. Importance of ethical communication strategies in fostering meaningful intercultural interactions and mutual respect among participants in a multicultural setting.